Rampak Genteng: Local Culture and Promotion by Public Relations - Firdaus, Sandrina Maharani; Kania, Niken; Erawati, Dedet (Asian Journal of Social and Humanities, 2025)
This research advances existing studies by examining how Jatiwangi Art Factory (JAF) utilizes unique public relations strategies to promote Rampak Genteng - a distinctive cultural event using roof tiles as an artistic medium, which previous research has not explored in depth. While prior studies have generally analyzed social media's role in cultural promotion, this study delves into context-specific tactics like workshops, school collaborations, and word-of-mouth advocacy that effectively overcame local institutional resistance. Applying Cutlip, Center, and Broom's (1952) PR theory to a grassroots context, the research demonstrates how these participatory communication strategies not only built community ownership but also achieved national recognition through inclusion in Kemenparekraf's KEN calendar, offering a valuable model for preserving intangible cultural heritage in the digital age that differs from broader cultural marketing approaches.